2016
DOI: 10.1111/jade.12055
|View full text |Cite
|
Sign up to set email alerts
|

An Autoethnographical Study of Culture, Power, Identity and Art Education in Post‐Colonial South Korea

Abstract: This article reflects my experiences of learning art in the 1970s and 1980s and my teaching career in school art education in twenty‐first century South Korea. This autobiographical reflection shows how I have struggled with my identity as an art teacher in the post‐colonial context of Western influences on Korean society since World War II. There has been greater tension and a greater struggle for different values, practices and identities when new values and practices have been introduced into the particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Shu, L. et al explored and analyzed the art teaching mode based on the technology of flipped classroom, which promotes the cultivation of personalized art thinking and the improvement of students' art skill level [12]. Zeng, S. affirmed the status quo of the application of multimedia technology and computeraided technology in teaching in colleges and universities, and proposed that the interaction of music and dance fitness can better show the charm of dance as well as the mood of music [13]. Wang, H et al revealed the trend of diversified development of fine arts in the 21st century, which significantly affects the ideas and teaching forms of oil painting teaching in colleges and universities, and listed in detail the innovative paths and development trends of oil painting teaching, which provides important references for oil painting teaching in colleges and universities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Shu, L. et al explored and analyzed the art teaching mode based on the technology of flipped classroom, which promotes the cultivation of personalized art thinking and the improvement of students' art skill level [12]. Zeng, S. affirmed the status quo of the application of multimedia technology and computeraided technology in teaching in colleges and universities, and proposed that the interaction of music and dance fitness can better show the charm of dance as well as the mood of music [13]. Wang, H et al revealed the trend of diversified development of fine arts in the 21st century, which significantly affects the ideas and teaching forms of oil painting teaching in colleges and universities, and listed in detail the innovative paths and development trends of oil painting teaching, which provides important references for oil painting teaching in colleges and universities [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the digital era, cultural education in colleges and universities is undergoing a profound change. This change involves not only the renewal of educational content and form but also the reshaping of the roles of educators and learners [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on visual art curricula also points to the significant role which visual art play in facilitating aesthetic gains and creating a common language in European countries (Kraehe et al, 2015). Furthermore, Jeong (2017), also emphasises that visual art courses had the potential to remove the borders between communities, joining them economically and culturally by creating awareness on universal values, without tampering national and local values.…”
Section: Introductionmentioning
confidence: 99%